ANALISIS COST EFFICIENCY PADA PERUSAHAAN PERBANKAN GO PUBLIC DI INDONESIA TAHUN 2008–2011 - Sisca Cicilia Susanto (Jurnal Universitas Paramadina, 2013)
AbstractThe objective of this research is to analyze the Cost Efficiency Ratio (CER) and performances of 24 banking firms listed at Indonesian Stock Exchange from year 2008 until 2011. The analysis of this study is descriptive analysis. The result of this study shows that the average of CER of the Banks is 72,2%. It indicates that most of the Banks have ineffective Cost Performance. By using CER stated owned banks were more efficient than commercial banks.Keywords: Cost Efficiency Ratio (CER), performance, Indonesian banks